An Analysis of Teaching Strategies in Reading Comprehension at 2nd Grade of a Junior High School in Bandung - Rahma Sakina; Salma Ramadanti Answar; Wulandari Putri (Gunung Djati Conference Series, 2023)
This research aims at analysing teaching strategies used by the teacher in reading comprehension class and investigating the problems the teacher encounter in their own reading comprehension class. The participants involved in this research are an English teacher and 8th grade students of SMPIT Asmaul Husna, a private school located in the Tanjungsari Sumedang. A descriptive qualitative study was used as a research design here. The data were obtained from classroom observation, interview with the teacher, and document analysis. The findings revealed that the teacher employed three strategies in teaching reading comprehension, namely scaffolding, question answer relationship, and think-aloud. Additionally, the study identified three problems overcome by the teacher in teaching reading comprehension, including difficulty in finding out the appropriate materials, the limited knowledge of effective instructional strategies, and difficulty in transferring personal reading comprehension skills to teaching practice. The findings of this research are expected to contribute to the understanding of effective reading comprehension instruction and provides valuable insights for teacher training and professional development programs.